Trade policy and foreign trade of the European Union - Larysa Grygorova-Berenda; Kateryna Kaverina (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2022)
Economic globalization is characterized by an increase in international trade and growing interdependence of economies at the global level. The EU's trade policy is a central tool for responding to the challenges associated with globalization and other modern challenges, such as the consequences of the pandemic and the full-scale Russian invasion of Ukraine, and turning its potential into real benefits. In other words, the trade policy of the European Union is a significant lever in shaping the competitiveness of the EU in the world market and is based on a wide range of various measures, which determines the relevance of this study. The subject of the study is the peculiarities and prospects of the development of trade policy and foreign trade of the European Union. In turn, the goal is to analyze the specifics of trade policy implementation and the current state of the European Union's foreign trade. It was found that bilateral international agreements play a decisive role among EU policies. But there are also unilateral policy measures that also have a huge impact on the state and performance of foreign trade. Among them are tariff and non-tariff regulation methods. It has been found that despite the fact that the EU's share of world trade has been falling in recent years, it remains at a high level and is a key basis for growth, competitiveness and employment in the EU. At the same time, the EU's export and import dynamics have a tendency to grow, which indicates that despite the decline in the EU's share in world trade, the EU's position as one of the world's trade leaders will strengthen, but competition will grow. To achieve the set goal and solve research tasks, modern methods of scientific research were used in the performance of scientific work, in particular, general scientific and special methods of analysis of economic phenomena and processes: systematic approach, comparative analysis, historical-logical method, comparative analysis, economic-mathematical modeling, and namely: trend analysis. Therefore, the growing indicators of the EU's foreign trade prove that the EU's trade policy is successful.